Comparison of non‐ablative and ablative fractional laser treatments in a postoperative scar study. Issue 10 (3rd November 2014) - Shin, Jung U; Gantsetseg, Dorjsuren; Jung, Jin Young; Jung, Inhee; Shin, Sungsik; Lee, Ju Hee
<x xml:space="preserve">Abstract</x> Background and Objective Postoperative scarring after thyroidectomy is a problem for both patients and clinicians. Recently, both non‐ablative and ablative fractional laser (NFL and AFL) systems have attracted attention as potential therapies for the revision of thyroidectomy scars. The present split‐scar study was designed to directly compare the efficacy of these two methods for the treatment of post‐thyroidectomy scars. Study Design/Materials and Methods Twenty females (mean age 42.1 years, range 22–55) with scarring 2–3 months post‐thyroidectomy were enrolled in the study. One half of the scar (chosen at random) was treated with NFL and the other half was treated with AFL. In each case, two treatments were given at 2‐month intervals. Clinical photographs were taken at baseline, before each treatment, and at the final 3‐month evaluation. Independent clinician grading of improvement and patient satisfaction were measured on a quartile scale. Color (erythema and melanin indices) and scar hardness were measured at baseline and at three months post‐treatment with a dermaspectrometer and durometer, respectively. Results The mean clinical improvement grades for AFL and NFL were highly similar, 2.45 ± 0.99 and 2.35 ± 0.85, respectively, without statistical significance (P = 0.752). However, NFL treatment resulted in statistically significant changes in erythema and pigmentation (P = 0.035 and P = 0.003, respectively), and skin hardness was significantly reduced after AFL treatment (P = 0.026). Conclusions Clinical improvement was not significantly different between the two systems; however, AFL was better at reducing scar hardness whereas NFL was superior for lightening color. These data suggest that a study assessing the feasibility of a combined approach for the revision of post‐thyroidectomy scarring might be warranted. Lasers Surg. Med. 46:741–749, 2014. © 2014 Wiley Periodicals, Inc.